A photocurable leaky dielectric for highly electrical insulating electrohydrodynamic micro-/nanopatterns. Issue 43 (20th September 2016) - Wang, Guolong; Lv, Guowei; Zhang, Shihu; Shao, Jinyou; Li, Xiangming; Tian, Hongmiao; Yu, Demei; Zhang, Lifeng
Abstract : An innovative photocurable leaky dielectric material is developed for high-performance electrohydrodynamic patterning towards highly electrical insulating micro-/nanopatterns. Abstract : This communication describes an innovative photocurable leaky dielectric for electrohydrodynamic patterning (EHDP). Based on the well-designed molecular structure, the material in its liquid state exhibits low viscosity, high homogeneity, and more importantly a leaky dielectric characteristic; meanwhile, UV light irradiation transforms it from a liquid leaky dielectric into a solid perfect dielectric instantaneously via an interfacial reaction. Two typical EHDP processes have confirmed that the beneficial properties of this material help to rapidly fulfill a higher aspect ratio and/or smaller feature size patterning compared to its perfect dielectric counterpart. Therefore, this material provides the potential in accessing high-performance EHDP towards fabricating electrically insulating micro-/nanostructures.